Survival after Major Cardiac Surgery: Performance and Comparison of Predictive Ability of EuroSCORE II and Logistic EuroSCORE in a Sample of Mediterranean Population - Arnáiz-García, María Elena; González-Santos, Jose María; López-Rodríguez, Javier; Dalmau-Sorlí, María José; Bueno-Codoñer, María; Arévalo-Abascal, Adolfo (The Thoracic and Cardiovascular Surgeon, 2014)
Background The European System for Cardiac Operative Risk Evaluation (EuroSCORE) II has been recently introduced to improve mortality prediction in cardiac surgery. We compare the predictive ability of the new EuroSCORE II with that of the original logistic EuroSCORE and we made an evaluation of a sample of our population submitted to major cardiac surgery in the context of a Mediterranean country.Materials and Methods Predicted and observed mortality were recorded in 1,200 consecutive patients undergoing major cardiac surgery at our institution with both logistic EuroSCORE and EuroSCORE II. Patients were grouped according to type of surgery: isolated valvular (n = 538), isolated coronary (n = 322), combined (n = 192), and miscellaneous (n = 148). Predictive capacity of both scales was compared for overall population and for each group in terms of calibration and discrimination using the observed by expected mortality rate, Hosmer–Lemeshow test, and C-statistic.Results Overall mortality was 6.8%, whereas that predicted by logistic EuroSCORE and EuroSCORE II was 9.7 and 3.7%, respectively. Mortality in our population was higher than mortality expected according to the original EuroSCORE II database. For all groups included in our population, logistic EuroSCORE overestimated mortality and EuroSCORE II underestimated the outcome even more. However, EuroSCORE II showed better calibration than logistic EuroSCORE for overall, valvular, and combined surgery. In contrast, logistic EuroSCORE demonstrated better calibration for coronary surgery. Discrimination capacity was good for both risk scores, but it was superior for logistic EuroSCORE than for EuroSCORE II in all considered subgroups unless combined surgery.Conclusion Mortality in our population was higher than the mortality that would have been expected by the new EuroSCORE II analysis. Although EuroSCORE II has good calibration and discrimination capacity, both are worse than those demonstrated by logistic EuroSCORE. Forthcoming evaluations are necessary when the new model will be widely used.
Keywords: cardiac; surgery; mortality; risk assessment